Validade, confiabilidade e responsividade da versão brasileira do instrumento World Health Organization Disability Assessment Schedule (WHODAS 2.0) em indivíduos com apneia obstrutiva do sono - Oliveira, Ana Cecília Silva de (2023)
Obstructive sleep apnea (OSA) is a sleep breathing disorder characterized by recurrent episodes of total or partial upper airway (UA) obstruction, with impairments unrestricted to sleep, but also during wakefulness. The World Health Organization Disability Assessment Schedule (WHODAS 2.0) is a generic instrument for assessing functioning, not yet validated for individuals with OSA. The aim of this study was to verify the validity, reliability and responsiveness of the WHODAS 2.0 instrument for individuals with OSA based on the analysis of psychometric properties. Methods: this is a methodological study to verify the validity, reliability, and responsiveness of the WHODAS instrument, with a sample of 100 individuals with OSA, using the following instruments: WHODAS 2.0 version of 36 items, the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index (PSQI), and the 12-item health survey (SF-12). The following psychometric properties were tested: internal consistency, convergent validity, discriminative validity, and responsiveness, with the latter being specifically applied to participants who started treatment with CPAP (continuous positive airway pressure) after initial assessment and were approached in a new moment of the research. Statistical analysis was performed using R and JAMOVI version 2.3. Internal consistency was calculated using Cronbach's alpha, convergent validity using Spearman's correlation coefficient through the correlation between the WHODAS 2.0 and the ESE, PSQI, and SF-12 instruments; the discriminative validity of OSA severity with functioning was assessed using the Kruskal- Wallis test and responsiveness to CPAP therapy was assessed using the Wilcoxon test. Results: the internal consistency value was considered satisfactory (α=0.76), considering the total score of the WHODAS 2.0 domains, except for the self-care domain, which showed unsatisfactory consistency. (α= 0.52). The results of convergent validity indicated an excellent correlation (r= -0.80) between the domains of functioning and quality of life. Discriminative validity showed no association between OSA severity degrees and functioning (p = 0.90) and responsiveness to CPAP treatment showed a large effect size (r = 0.82) with p < 0.05. Conclusion: The WHODAS 2.0 instrument is valid, reliable, and responsive for assessing individuals with OSA.